Initial and subsequent location choices of immigrants to the Netherlands - Aslan Zorlu; Clara H. Mulder (Institute for the Study of Labor (IZA), 2007)
The initial settlement behaviour and the subsequent mobility of immigrants who arrived in the Netherlands in 1999 are examined using rich administrative individual data. The study considers the settlement patterns of immigrants from various countries of origin who entered the country as labour, family or asylum migrants. The evidence suggests distinct settlement trajectories for asylum and other non-western immigrants. The presence of co-ethnics and members of other ethnic minorities, but also socioeconomic neighbourhood characteristics, appear to play an important role in determining location choice. Differences in the settlement and spatial mobility patterns of immigrants with various degrees of distance from the native Dutch in terms of human and financial capital, proficiency in the relevant language(s), and religion confirm the main predictions of spatial assimilation theory.
Keywords: 330; Location choice; immigrants and ethnic residential segregation; Migranten; Einwanderung; Wohnstandort; Segregation; Niederlande